ENSINO HÍBRIDO NA EDUCAÇÃO BÁSICA: NARRATIVAS DOCENTES SOBRE A ABORDAGEM METODOLÓGICA NA PERSPECTIVA DA PERSONALIZAÇÃO DO ENSINO - CANNATÁ, VERÔNICA MARTINS (2017)
The central theme of this research is the pedagogical practice as reference of a formal education program. The research has as general objective to reflect on the insertion of blended learning from the angle of the teacher that acts as mediator and focuses on personalization and on technology integration to the curriculum. In relation to specific objectives, and regarding both experiences here narrated and the interlacing of the stories (participants and researcher), we analyze the points of interconnection with the challenges, the afflictions and the discoveries of a teacher in view of the use of DICT (Digital Information and Communication Technologies) in the promotion of knowledge construction. This is a qualitative investigative research elaborated in the autobiographical narrative modality and supported by hermeneutic-phenomenological approach for interpretation of learning narratives, considering that the description of phenomena leads to the essence of lived experience. With inspiration in the narrative research of Clandinin and Connelly (2011), this study is based on the theoretical principles of the biographical approach of Delory-Momberger (2012), Passeggi (2011) and Larrosa (1999), as well as on the hermeneutic-phenomenological formulation of M. Freire (2012). The theoretical contributions are based on the following authors: Horn and Staker (2015); Zabala (1998); Mizukami (1986); Moran (2015); Costa (1989); Almeida and Valente (2011); Perrenoud (2013); Santos (1994); Vieira Pinto (2005) and Vygotsky (1997). The research also presents a brief historical review of traditional school and active learning, besides covering didactic strategies of learning spaces reconfiguration and teaching challenges in the contemporary world. Technology, knowledge and personalization are contextually addressed as concept, instrument and support for the efficient use of data in blended learning, without losing sight of the application of intelligence technologies. Finally, we seek to identify the perceptions of teachers of basic education __ for example, in relation to teaching practice and technology __ from public and private networks, regarding the use of digital media in pedagogical practices and the promotion of learning using blended learning.